Computational analysis of the influence of drusen growth on the morphology of RPE due to Age‐related Macular Degeneration. Issue 1 (25th January 2021) - Holla, Vijaya; Timothy, Jithender J.; Meschke, Günther
Abstract: Age‐related macular degeneration (AMD) is a disease that affects the macular region of the outer retina. AMD is characterized by the presence of large extracellular debris called drusen between the Bruch's Membrane (BrM) in the choroid and the retinal pigment epithelium (RPE) in the outer retina. An important feature of AMD is the degenerative changes in the RPE and the photoreceptors that leads to the deterioration and loss of central vision. In this contribution, the effect of drusen size on the morphological changes in the RPE, BrM and photoreceptors are investigated using the cellular potts model (CPM) and machine learning. Numerical simulation of the influence of drusen growth and its effect on the morphology of the outer retinal layers of the macula is presented and the implications for AMD progression discussed.